2007
DOI: 10.1111/j.1526-4637.2006.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Fentanyl Reduces Pain and Improves Functional Activity in Neuropathic Pain States

Abstract: Overall, there was a significant reduction in pain intensity and increase in activity in neuropathic pain patients treated with transdermal fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…After one week of fentanyl administration, locomotor activity increased for all fentanyl-treated animals. These results suggest that sedation may not be a major concern with chronic fentanyl administration, and similar results have been observed in clinical setting with human patients (Agarwal et al 2007). Interestingly, activity levels continued to increase throughout the drug treatment period, and these increases in activity were lowest in the oldest animals (although by week 4 activity levels were similar across ages), suggesting that opioids have a diminished effect with increasing age.…”
Section: Discussionsupporting
confidence: 86%
“…After one week of fentanyl administration, locomotor activity increased for all fentanyl-treated animals. These results suggest that sedation may not be a major concern with chronic fentanyl administration, and similar results have been observed in clinical setting with human patients (Agarwal et al 2007). Interestingly, activity levels continued to increase throughout the drug treatment period, and these increases in activity were lowest in the oldest animals (although by week 4 activity levels were similar across ages), suggesting that opioids have a diminished effect with increasing age.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that the therapeutic use of opioids can be associated with altered cognition and impaired psychomotor function, particularly when first administered (Chapman et al, 2002; Kamboj et al, 2005). However, some studies reach the opposite conclusion when these medications are used long-term (Agarwal et al, 2007; Gaertner et al, 2006), even with reports of improved cognition (Lorenz et al, 1997; Panjabi et al, 2008). Concordantly, Brown and colleagues (Brown et al, 2006) developed a regression model in which psychological factors and pain severity predicted the decline in cognitive function better than specific opioid medications or daily opioid dose.…”
Section: Discussionmentioning
confidence: 99%
“…Khallouk-Bousselmame & Costentin, 1994; Powell & Holtzman, 2001; Rauhala et al, 1995; Trujillo et al, 2004). Clinically, extended fentanyl administration increases activity, although it is unclear if this is a direct effect of fentanyl or a by-product of mitigation of chronic pain in these patients (Agarwal et al, 2007). Age-related decreases in rotarod performance were maintained throughout all phases of drug/saline administration, however fentanyl did not influence performance.…”
Section: Discussionmentioning
confidence: 99%